2022
DOI: 10.1186/s12870-022-03699-2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and regulation of anthocyanins in white and purple Tibetan Hulless Barley (Hordeum vulgare L. var. nudum Hook. f.) revealed by combined de novo transcriptomics and metabolomics

Abstract: Background Colored barley, which may have associated human health benefits, is more desirable than the standard white variety, but the metabolites and molecular mechanisms underlying seedcoat coloration remain unclear. Results Here, the development of Tibetan hulless barley was monitored, and 18 biological samples at 3 seedcoat color developmental stages were analyzed by transcriptomic and metabolic assays in Nierumuzha (purple) and Kunlun10 (white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 64 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…f), a common barley species belonging to the wheat family gramineae, is also called hulless barley or naked barley because its lemma and palea are separated during harvesting [ 1 ]. The Qinghai–Tibet Plateau is the main cultivation area of Qingke, and it is distributed in the plateau areas at elevations of 2400–4500 m [ 1 ]. It is one of the main food crops for the people in Tibet.…”
Section: Introductionmentioning
confidence: 99%
“…f), a common barley species belonging to the wheat family gramineae, is also called hulless barley or naked barley because its lemma and palea are separated during harvesting [ 1 ]. The Qinghai–Tibet Plateau is the main cultivation area of Qingke, and it is distributed in the plateau areas at elevations of 2400–4500 m [ 1 ]. It is one of the main food crops for the people in Tibet.…”
Section: Introductionmentioning
confidence: 99%
“…The central biosynthetic pathway producing anthocyanin has been well studied previously ( Koes et al., 2005 ). Previous studies have identified multiple anthocyanin biosynthesis genes ( PAL , C4H , 4CL , CHS , CHI , F3H , F3’H , DFR , ANS , GT , and ACT ) showing the significantly higher expression in colored qingke, and their expression was strongly correlated with the content of anthocyanins ( Yao et al., 2022 ). It is important to note that the initial steps to generate anthocyanin have been well-studied.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating transcriptomic and metabolomic analyses in wheat has revealed that variations in anthocyanin content are highly linked to the differential expression of key structural genes, such as TaCHS and TaANS, in the anthocyanin biosynthesis pathways (Wang et al, 2021). Yao et al (2022) also identified a series of structural genes and transcription factors in anthocyanin pathways showing the differential expression between purple and white qingke seeds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations